The sounds of feminist theory - Salvaggio, Ruth (SUNY series in feminist criticism and theory., 1999)
In The Sounds of Feminist Theory, Ruth Salvaggio follows a distinctive turn toward the oral and evocative qualities of language in feminist theory. Questioning paradigms of female voice and varied feminist claims to language, she suggests that feminist theorists listen to the ways in which words mean more than they ostensibly signify, the ways in which language and epistemology - like sound - are mobile. She calls this theoretical project "Hearing the O," a process of listening for and seizing those wavering qualities of language that invite changes, often remarkable alterations, in how we think